To stream or not to stream? exploring factors influencing impulsive consumption through gastronomy livestreaming - Yu, Cheng; Cheah, Jun Hwa; Liu, Yide (Emerald, 2022)
Purpose: In China, the practice of livestreaming while shopping has evolved from a form of entertainment into a new business strategy. In recent years, the gastronomy industry has also adopted livestreaming as a means of online promotion. Based on the stimulus–organism–response theoretical model, this study aims to investigate the effects of gastronomy livestreaming on viewers’ impulsive consumption by considering gamification, perceived professionalism and telepresence as causative factors. Design/methodology/approach: This study conducted a survey of gastronomy livestreaming viewers that received 1,093 responses. The effects of gamification, perceived professionalism and telepresence were then analyzed using partial least squares-path modeling and necessary condition analysis. Findings: This study finds that gamification, perceived professionalism and telepresence are sufficient conditions for explaining impulsive consumption. Innovativeness mediates the relationships between these factors and impulsive consumption. Furthermore, gamification and innovativeness represent necessary conditions for impulsive consumption. Practical implications: The findings of this study contribute to an enhanced understanding of livestreaming in the gastronomy industry. Based on these findings, managers in the gastronomy industry can use more interactive gamification activities and enhance telepresence to increase viewers’ impulsive consumption during livestreaming sessions. Originality/value: This study identifies the modalities through which gastronomy livestreaming can stimulate impulsive consumption. This is an early study to investigate the effect of experiences of gamification, perceived professionalism and telepresence on viewers’ impulsive consumption in the context of gastronomy livestreaming. In addition, this early study investigates the effect of gastronomy livestreaming innovativeness on impulsive consumption.